2012
DOI: 10.2478/10004-1254-63-2012-2137
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sleepiness: The Role of the Arousal System

Abstract: It is generally accepted that two basic physiological processes regulate sleepiness: homeostatic and circadian rhythmic processes. Recent research has proposed the third component regulating sleepiness, that is, the wake drive or the arousal system. The role of the arousal system in regulating sleepiness has partly been addressed by the studies of the pathophysiology of insomnia, which is often described as a disorder of hyperarousal. Experimental and correlational studies on the relation between sleepiness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 102 publications
0
4
0
2
Order By: Relevance
“…Most prominent among these pathways was the wellestablished hypocretin arousal pathway 53 (including missense variants in HCRTR1, HCRTR2, and TRPC6). It is thus possible that orexin receptor agonism, a therapeutic strategy currently under investigation for narcolepsy, may have roles in the treatment of patients with more mild deficits in the arousal/wake drive system 54 . Additional pathways with known roles in sleep-wake biology in model organisms 55 include neuronal excitability driven by variation in the function of potassium channels and glutamate signaling, EGFR signaling pathway, and opioid signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Most prominent among these pathways was the wellestablished hypocretin arousal pathway 53 (including missense variants in HCRTR1, HCRTR2, and TRPC6). It is thus possible that orexin receptor agonism, a therapeutic strategy currently under investigation for narcolepsy, may have roles in the treatment of patients with more mild deficits in the arousal/wake drive system 54 . Additional pathways with known roles in sleep-wake biology in model organisms 55 include neuronal excitability driven by variation in the function of potassium channels and glutamate signaling, EGFR signaling pathway, and opioid signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Neural activity within the locus coeruleus positively correlates with pupil size (e.g., Joshi, Li, Kalwani, & Gold, 2016;Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, 2014) and it has been shown that optimal task performance is associated with an intermediate activity level of this nucleus, with hypoactivation leading to attentional lapses caused by low alertness and arousal, and hyperactivation leading to task disengagement caused by anxiety and distractibility (Aston-Jones & Cohen, 2005;Cohen, Aston-Jones, & Gilzenrat, 2004). Given the close relation between arousal and daytime sleepiness (Bakotić & Radošević-Vidaček, 2012), it is likely that the reduced and variable pupil diameters that are observed during mind-wandering correspond to increased fatigue and sleepiness. However, to date, no study has assessed pupil parameters in relation to taskunrelated thoughts and daytime sleepiness within the same experimental paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Pospanost je fiziološki fenomen koji odražava potrebu za spavanjem, a regulisan je ciklusom spavanje -budnost [8]. Prekomerna pospanost se definiše kao visoka sklonost ka spavanju u situacijama povezanim sa dnevnim funkcionisanjem, kao što su radne, školske i kognitivne aktivnosti tokom kojih se očekuje da osoba bude budna i pažljiva [8].…”
unclassified
“…Pospanost je fiziološki fenomen koji odražava potrebu za spavanjem, a regulisan je ciklusom spavanje -budnost [8]. Prekomerna pospanost se definiše kao visoka sklonost ka spavanju u situacijama povezanim sa dnevnim funkcionisanjem, kao što su radne, školske i kognitivne aktivnosti tokom kojih se očekuje da osoba bude budna i pažljiva [8]. Uzrok prekomerne dnevne pospanost kod studenata može biti i loša higijena spavanja, koja uključuje konzumaciju alkohola, kafe ili energetskih napitaka, upotrebu kompjutera, tablet računara ili mobilnih telefona i sprovođenje drugih ometajućih aktivnosti neposredno pred spavanje [9,10].…”
unclassified